Solubilization of Charged Porphyrins in Interpolyelectrolyte Complexes: A Computer Study - Šindelka, Karel; Limpouchová, Zuzana; Procházka, Karel (Polymers, 2021)
Using coarse-grained dissipative particle dynamics (DPD) with explicit electrostatics, we performed (i) an extensive series of simulations of the electrostatic co-assembly of asymmetric oppositely charged copolymers composed of one (either positively or negatively charged) polyelectrolyte (PE) block A and one water-soluble block B and (ii) studied the solubilization of positively charged porphyrin derivatives (P+) in the interpolyelectrolyte complex (IPEC) cores of co-assembled nanoparticles. We studied the stoichiometric mixtures of 137 A10+B25 and 137 A10-B25 chains with moderately hydrophobic A blocks (DPD interaction parameter aAS=35) and hydrophilic B blocks (aBS=25) with 10 to 120 P+ added (aPS=39). The P+ interactions with other components were set to match literature information on their limited solubility and aggregation behavior. The study shows that the moderately soluble P+ molecules easily solubilize in IPEC cores, where they partly replace PE+ and electrostatically crosslink PE- blocks. As the large P+ rings are apt to aggregate, P+ molecules aggregate in IPEC cores. The aggregation, which starts at very low loadings, is promoted by increasing the number of P+ in the mixture. The positively charged copolymers repelled from the central part of IPEC core partially concentrate at the core-shell interface and partially escape into bulk solvent depending on the amount of P+ in the mixture and on their association number, AS. If AS is lower than the ensemble average ⟨AS⟩n, the copolymer chains released from IPEC preferentially concentrate at the core-shell interface, thus increasing AS, which approaches ⟨AS⟩n. If AS>⟨AS⟩n, they escape into the bulk solvent.
Keywords: porphyrin; IPEC; electrostatic co-assembly; solubilization; computer simulations